(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Monetary returns (15.4%) and well packaged schemes withall benefits (15.2%), (choice of hospitals, choice of doctors, electivesurgery, ambulance, all medical costs, medical and hospital expenses incurredoverseas, and other ancillary services) are other main attributes preferred bythe respondents. Attribute like easy paying installments is preferred by12.2percent of the respondents followed by lesser paper work (9.1%) and relevant inway of simple terms and conditions (7.6%), availability (6.2%), simple language(5.5%), transparent (4.1%), convenience (3.5%), and quality of service (3.5%)are other preferred attributes for future health insurance policies. consumersprefer low premium with more benefits schemes and returns. The policies shouldbe simple as complexity results in raising suspension in the customers mindsand delays decisions. The customers should get policies on time as, afterascertaining the potential, creating a market and devising a product, it wouldbe unfortunate if the customer does not get the product because of the lack ofavailability.